Relationship Between Parenting Style and Student Creativity and Implications for Guidance and Counseling Services - Yulna Gustia; Indah Sukmawati (Universitas Negeri Padang, 2019)
One of the goals of education is to develop the potential of students to be creative human beings. However, in reality in the field there are still students who have not shown the characteristics of creativity such as not having great curiosity, there are still students who have not been able to make their own decisions, and parents who restrict children from choosing extracurricular activities. Creativity is an ability that is owned by students who are different from others (unique) in solving a problem and it is suspected that one of the factors that influence it is parenting parents. This research is a descriptive correlational research with quantitative methods. The total sample of 256 students was selected using the Stratified Proportional Random Sampling technique. The research instruments used were parenting questionnaires and student creativity questionnaires. The results revealed that (1) the parenting style applied by parents to their children in Padang N 2 High School was mostly authoritative parenting (2) the creativity of students in Padang N 2 High School as a whole was quite creative (3) there was a significant relationship between parenting parents with students' creativity in Padang N 2 High School. Based on the research findings, it is recommended that school counselors / counselors be able to provide guidance and counseling services, namely information services and individual counseling services in order to help students who have problems regarding creativity.